An investigation of temperature effect on incremental forming - Echrif, Salah B. M.; Hrairi, Meftah (2013)
metal change with an increase in temperature. For these reasons it is very important to investigate the temperature effect on the manufactured part by incremental forming. In the present paper, the temperature is investigated numerically through finite element simulation and experimentally using thermography nondestructive technique. Both experimental and numerical results are in close agreement. It was found that the maximum temperature among the forming passes reached experimentally 62 °C and numerically 68 °C at which the properties does not change. Therefore, it is considered as low temperature compared to conventional forming processes like deep drawing. Thus, it can be concluded that temperature effect on material properties in incremental forming process can be neglected.